Assessment of Knowledge, Attitude and Practices Regarding Life Style Modification among Type 2Diabetic Mellitus Patients Attending Adama Hospital Medical College, Oromia Region, Ethiopia (Global Journal of Medical Research, 2015)
Abstract not found
Keywords: type 2 diabetes mellitus; life style modification; knowledge; attitude; practice